"Making a good time": The role of friendship in living successfully with aphasia. (April 2013) - Brown, Kyla; Davidson, Bronwyn; Worrall, Linda E.; Howe, Tami
Abstract Loss of friendship post-onset of aphasia is well documented, with reduced social network size and social isolation commonly reported. Because friendship has strong links to psychological well-being and health, increased knowledge about friendships of individuals with aphasia will have important clinical implications. This study aimed to explore the perspectives of 25 community dwelling individuals with chronic aphasia on the role of friendship in living successfully with aphasia. Thematic analysis of transcripts from semi-structured in-depth interviews revealed three over-arching themes relating to the role of friendship in participants' experience of life with aphasia: living with changes in friendships, good times together and support from friends, and the importance of stroke and aphasia friends. Overall, findings highlighted the valued role of friendship in living successfully with aphasia, while also providing evidence of how friendships change and evolve in both negative and positive ways following onset of aphasia. Clinicians are challenged to work creatively to address the role of friendship in life post-stroke in partnership with individuals with aphasia, their families, and friends.